2019
DOI: 10.1016/j.addbeh.2019.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Reasons to use e-cigarettes among adults and youth in the Population Assessment of Tobacco and Health (PATH) study

Abstract: Background: While e-cigarette use is increasing, reasons to use e-cigarettes are poorly summarized in the literature. The objective of this study was to organize reasons to use e-cigarette items into factors and determine associations between these factors and e-cigarette user characteristics. Methods: Data were drawn from youth (12–17) and adults (18+) in Wave 1 (2013–2014) of the Population Assessment of Tobacco and Health (PATH) study. Exploratory factor analysis was conducted on 13 reasons to use survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Participants reported using e-cigarettes primarily as an aid to quit smoking (35%) and as a healthier alternative to combustible cigarettes (32%). This is consistent with current established adult e-cigarette users from Wave 1 of the PATH study (2013-2014) who also reported using e-cigarettes as an alternative to cigarettes 17 . Interestingly, women in our study were less inclined to reduce their nicotine e-liquid concentrations compared to men.…”
Section: Discussionsupporting
confidence: 84%
“…Participants reported using e-cigarettes primarily as an aid to quit smoking (35%) and as a healthier alternative to combustible cigarettes (32%). This is consistent with current established adult e-cigarette users from Wave 1 of the PATH study (2013-2014) who also reported using e-cigarettes as an alternative to cigarettes 17 . Interestingly, women in our study were less inclined to reduce their nicotine e-liquid concentrations compared to men.…”
Section: Discussionsupporting
confidence: 84%
“…People vape for a variety of reasons, including as a partial or complete substitute for cigarettes or other tobacco products, a belief that e-cigarettes are less harmful than cigarettes, and the ability to vape in places where other types of tobacco use is prohibited, 7 including workplaces. 8 , 9 Such use may be due to the legal permissibility and social acceptance of vaping, or because vaping can be done “stealthily” to avoid detection.…”
mentioning
confidence: 99%
“…In 2018, 14.9% of adults in the United States reported ever using an e-cig, and 3.2% reported current use [ 8 ]. Many adults report initiating e-cig use as a way to quit cigarette smoking [ 9 , 10 ]; however, the impact of e-cig use on quitting smoking has been controversial in the literature [ 11 , 12 , 13 ]. Some studies have reported that e-cig use is not associated with increased success in quitting [ 14 , 15 ], while other studies have found that e-cigs can be effective aids in quitting [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%